The role of national culture on the relationship between leadership styles and job satisfaction among public universities in the United Arab Emirates - Al Hammadi, Ali Hassan Yousif (2021)
Academic staff’s roles and responsibilities contribute to the improvement of the quality of higher education in the United Arab Emirates (UAE). Previous research has shown that leaders play a vital role in enhancing job satisfaction among academic staff. Here, transformational and transactional leadership were found to be the most efficiently influence attaining job satisfaction compared to other leadership styles. Due to the dynamic setting, the complexity and paradox of the society, and in response to globalization, job satisfaction among faculty members needs continuous adjustments to remain appropriate to the needs of the UAE public university. The need to develop a better leadership styles are becoming increasingly important in every organization. Leaders in any organization influence their subordinates using different types of leadership styles while national culture provides and additional value in the process. Thus, this study examine the mediating role of the national culture (power distance, collectivism, uncertainty avoidance, masculinity and long-term orientation) on the relationship between leadership styles (transformational, transactional and laissez-fair leadership style) and job satisfaction among academic staff in public universities in the UAE. Therefore, a quantitative approach was used in this study and therefore, a structured questionnaire with a 5-point Likert scale was used as the instrument of data collection with a total of 326 respondents from the academic staff in the UAE public universities. Here, the Statistical Package for Social Sciences (SPSS) and the Partial Least Square Structural Equation Modeling (PLS-SEM) were used to provide answer the raised from research objective and to test the hypotheses of the study. The results revealed that national culture mediate the relationship between, transformational leadership style, transactional leadership style, laissez-fair leadership style, and Job satisfaction. Thus, future studies on leadership styles and job satisfaction would undoubtedly lead to the growth and development of many organizations, particularly, in the higher education institutions.